Menopause, A Universal Female Experience: Lessons from Mexico and Central America - Locklear, Tracie D. (2008)
Publisher copyright policies & self-archiving: Author's Pre-print: author can archive pre-print (ie pre-refereeing). Author's Post-print: subject to Restrictions below, author can archive post-print (ie final draft post-refereeing). Restrictions:12 months (unless federal, government, funding agencies or local policy mandates for the author's institute a different policy on self-archiving). Publisher's Version/PDF: author cannot archive publisher's version/PDF.